2018
DOI: 10.5114/wiitm.2018.77269
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study comparing 5-year results between superobese and non-superobese patients after laparoscopic adjustable gastric banding.

Abstract: IntroductionLaparoscopic adjustable gastric banding (LAGB) is considered to be the least invasive, reversible, and the safest bariatric operation regarding mortality and morbidity, and its application to high-risk superobese (SO) individuals seems rational.AimThere are differing viewpoints regarding the effectiveness of LAGB in superobese (BMI > 50 kg/m2) patients. The aim of this study was to compare the safety and efficacy of LAGB in SO and non-superobese (NSO) patients in the long term (> 5 years).Material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…The %EWL at 5 and 10 years was 30% and 16.9%, respectively, while LAGB failure occurred in 57% of patients, and a higher baseline BMI was the only independently associated factor. In a recent prospective study comparing 5-year results between superobese and non-superobese patients after LAGB, the authors demonstrated that LAGB could lead to long-lasting weight loss after 5 years, but superobese patients had significantly inferior weight loss results than patients with a BMI ≤ 50 [28].…”
Section: Discussionmentioning
confidence: 99%
“…The %EWL at 5 and 10 years was 30% and 16.9%, respectively, while LAGB failure occurred in 57% of patients, and a higher baseline BMI was the only independently associated factor. In a recent prospective study comparing 5-year results between superobese and non-superobese patients after LAGB, the authors demonstrated that LAGB could lead to long-lasting weight loss after 5 years, but superobese patients had significantly inferior weight loss results than patients with a BMI ≤ 50 [28].…”
Section: Discussionmentioning
confidence: 99%